Wired: Energy Drinks, Jock Identity, Masculine Norms, and Risk Taking - Miller, Kathleen E. (2008)
OBJECTIVE: The author examined gendered links among sport-related identity, endorsement of conventional masculine norms, risk taking, and energy-drink consumption. PARTICIPANTS: The author surveyed 795 undergraduate students enrolled in introductory-level courses at a public university. METHODS: The author conducted linear regression analyses of energy-drink consumption frequencies on sociodemographic characteristics, jock identity, masculine norms, and risk-taking behavior. RESULTS: Of participants, 39% consumed an energy drink in the past month, with more frequent use by men (2.49 d/month) than by women (1.22 d/month). Strength of jock identity was positively associated with frequency of energy-drink consumption; this relationship was mediated by both masculine norms and risk-taking behavior. CONCLUSIONS: Sport-related identity, masculinity, and risk taking are components of the emerging portrait of a toxic jock identity, which may signal an elevated risk for health-compromising behaviors. College undergraduates’ frequent consumption of Red Bull and comparable energy drinks should be recognized as a potential predictor of toxic jock identity.